Gauchos and Foreigners : Glossing Culture and Identity in the Argentine Countryside. - Huberman, Ariana (Rowman & Littlefield Pub. Group, 2011)
In Gauchos and Foreigners: Glossing Culture and Identity in the Argentine Countryside Ariana Huberman discusses the relationship between the gaucho figure and the "foreigner" in Argentine rural literature. The narratives of William Henry Hudson, Benito Lynch and Alberto Gerchunoff present English scientists and travelers, as well as Jewish and Italian immigrants, in direct contact with the gaucho in the Argentine and Uruguayan countryside. The book shows how the intent to define and translate termsfrom the national glossary the gaucho, his lifestyle and habitat and from "foreign" cultures, ult.